Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Evaluation of anti-desmoglein-2 antibodies and cardiac biomarkers in Boxer dogs with arrhythmogenic right ventricular cardiomyopathy - L. Dos Santos; S. Cunningham; M. Mantovani (Journal of Veterinary Cardiology, 2026)

Diversity of convolutid acoels (Convolutidae, Acoela) in Hokkaido, Japan, including a description of the symbiont-bearing Amphiscolops ranshimensis n. sp. - Siratee Riewluang; Regine C. Manglicmot; Shaun Cunningham; Matthew D. Hooge; Rintaro Ono; Hiroshi Kajihara; Brian S. Leander; Kevin C. Wakeman (Zoologischer Anzeiger, 2026)

Behavioural responses to heat in an arid-zone bird vary with thermal, hygric and social factors - J. R. D. Whyte; A. E. McKechnie; J. K. Crossley; S. J. Cunningham (Oecologia, 2026)
The severity of fitness costs resulting from behavioural trade-offs between heat dissipation and activities such as foraging is increasing with advancing climate change. In terrestrial habitats, shade and water may buffer individuals from the negative effects of heat exposure, as may load-lightening in group-living species. We tested the hypothesis that thermal and hygric properties of home ranges (shade and water availability) and social factors (group size) influence the costs associated with hot weather, using a population of white-browed sparrow-weavers ( Plocepasser mahali ) in the southern Kalahari Desert. Across all sparrow-weaver groups, heat avoidance (shade-seeking) and dissipation (panting) behaviours increased with increasing air temperature ( T air ), whereas foraging declined. Birds occupying shadier home ranges delayed the onset of panting to higher T air and foraged less while maintaining overall peck rates. Birds with access to water foraged more, maintained higher peck rates and sought shade at higher T air compared to birds without. However, they did not pant more, making the mechanism underpinning their increased foraging effort unclear. Birds in larger groups both panted more overall and sought shade at lower T air than birds in smaller groups but maintained similar overall peck rates. Taken together, these results suggest birds in shadier home ranges can forage more efficiently, buffering foraging costs at high T air . Our data therefore suggest that some impacts of increasing T air under climate change can be buffered by shade availability, but the impacts of water availability and social factors are less clear.

Numerical and experimental investigations into the mechanical behaviour of compacted stranded copper conductors used in dynamic subsea power cables - Dominic M. Smith; Lee S. Cunningham; Lujia Chen (Ocean Engineering, 2026)

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Forward osmosis followed by reverse osmosis for the removal of contaminants of emerging concern using a CO2-responsive draw agent - Rachel S. Korchinsky; José Giovanni L. Brito; Louis Fieldhouse; Pascale Champagne; Michael F. Cunningham; Philip G. Jessop (Journal of Hazardous Materials, 2025)

Assessing structural resilience of masonry chamber-housed substations subject to flood flow and debris impact - Wenzhu Li; Lee S. Cunningham; David M. Schultz; Sarah Mander; Chin Kim Gan; Mathaios Panteli (Innovative Infrastructure Solutions, 2025)
Chamber-housed substations are a common substation type, essential for voltage regulation, load balancing, and fault isolation to ensure power supply grid stability and reliability. As typically ground-based structures, chamber-housed substations are vulnerable to damage from flooding. In the case of chambers constructed from plain masonry, these may be susceptible to structural damage from forces generated by flood flows. Although previous studies have examined substation failures based on flood levels, they often overlook the structural damage caused by moving floodwaters and floating debris, thereby underestimating risks and overestimating substation resilience. The present study introduces an analytical framework that uses computational fluid dynamics (CFD) coupled with finite element (FE) analysis to predict flood forces and structural responses in a level of detail that would hitherto not be possible with existing design code approaches. The CFD-based modelling approach was validated against existing hydraulic experiments and subsequently applied to a case study of a typical masonry chamber-housed substation in Malaysia, a country prone to severe annual flooding. The results reveal that substation walls can withstand flood velocities up to 10 m/s without debris. However, the presence of debris leads to damage at velocities below 2 m/s, highlighting a significant reduction in resilience. Fragility and risk curves, derived from a normalised Weibull function, further reveal that ignoring debris impact underestimates forces on walls by 60% to 83%. These findings highlight the need to update design guidelines to account for debris impact and to develop suitable retrofitting strategies for existing chambers.

The Evaluation of Macronutrient Composition of Maternal Breast Milk and Pasteurized Donor Breast Milk to Optimize Nutrition and Growth for the NICU Infant - S. Dave; L. Cunningham (Journal of the Academy of Nutrition and Dietetics, 2025)

A Review of Methionine and Cysteine: Their Roles as Sinks for Reactive Oxygen and Nitrogen Species, Including Bioinformatic Analysis of Their Percent Compositions in Metabolic Proteins - Bethany F. Laatsch; Burhan A. Ali; Anna R. Berthiaume; Grace C. Cunningham; Sabrina M. Duncan; Nathan Hau; Audrey Ho; Marais A. Loomis; Harrison R. Lowater; Brenya L. McNally; Kate L. Mueller; Matt Poppitz; et al. (Indian Journal of Clinical Biochemistry, 2025)

High satiety: Evaluating determinants of energy compensation and intake in multiple preloading studies - Barbara J. Rolls; Liane S. Roe; Paige M. Cunningham; Kathleen L. Keller; Faris M. Zuraikat (Appetite, 2025)

Optimising CFRP strengthening for RC columns subject to axial compression and lateral impact: an experimental study - Abdulrahman A. Almatrafi; Lee S. Cunningham; Zhangjian Wu (Innovative Infrastructure Solutions, 2025)
In a typical frame building, columns can be vulnerable to impact arising from accidental actions such as vehicular collisions. Depending on the nature of the structure and its degree of robustness, failure of a column under impact may lead to progressive collapse. In the case of reinforced concrete (RC) frames, various options exist for strengthening existing columns against impact, including the use of externally bonded carbon fibre reinforced polymer (CFRP). Whilst the application of CFRP in static loading situations has been extensively investigated, comparatively little research has been undertaken on the use of this strengthening method for lateral impact situations. Importantly, for the case of square columns, the effect of the axial loading ratio on the strengthened column’s impact response has not been fully investigated, nor has the identification of optimum CFRP strengthening configurations. The present work details an experimental investigation in which nine RC square columns were tested under lateral impact and co-existing axial compression using a purpose-built test rig incorporating a drop hammer and disc spring pile. Axial compression ratios of 5%, 25% and 50% in relation to the theoretical axial capacity of the column as predicted by Eurocode 2 were investigated. Similarly, a number of practically driven CFRP configurations were examined with a view to the identification of optimum strengthening. The test series revealed the axial compression ratio to be inversely proportional to the lateral displacement resulting from impact. As an alternative to full wrapping of the column member, the use of discrete bands of CFRP was found to produce comparable levels of performance in terms of lateral displacement and crack limitation, whilst resulting in a ~ 40% saving in CFRP material. Both full wrapping and discrete banding achieved at least a 30% reduction in displacement compared to the corresponding un-strengthened member.

Long-term trajectories of impacts and recovery of headwater stream temperatures after forest harvest in interior British Columbia - Douglas C. Braun; Dylan S. Cunningham; Herb E. Herunter; Sean M. Naman; Amanda M. Martens (Forest Ecology and Management, 2025)

Large urban trees are keystone structures for Australian microbats - Cara R. Parsons; Maldwyn J. Evans; Darren S. Le Roux; Saul A. Cunningham; Brad Law; Philip Gibbons (Biological Conservation, 2025)

What a load of rubbish: The impact of anthropogenic litter on urban freshwater diversity - Victoria S. Milner; Matthew J. Hill; Kieran J. Gething; Summer B. Cunningham (Environmental Pollution, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Advancing investigations into the effects of sweet and bitter tastes on agreeableness and hostility - Rachel S. Herz; Caitlin M. Cunningham; Theresa L. White (Food Quality and Preference, 2024)

Shore-Side Downfall Pressures Due to Waves Impacting a Vertical Seawall: An Experimental Study - Annelie Baines; Lee S. Cunningham; Benedict D. Rogers (Journal of Marine Science and Engineering, 2024)
As part of an investigation into downfall impacts from violent overtopping waves, experimental data are presented for the impact pressures and forces generated by regular and focused waves breaking onto a vertical wall and impacting a landward horizontal deck at a scale of 1:38. Particular attention is given to the wave-by-wave uprush and impact downfall events. By selecting regular and focused wave conditions that produce impacts, new trends are identified for violent downfall phenomena that could easily be underestimated in current practice. The characteristics of the downfall impacts are investigated and three different types of downfall impact are identified and discussed. Using a Wavelet Filter to denoise the signal from pressure probes without losing the peak impact pressures or introducing a phase shift, the distinctive features and dynamic behaviours of the white-water impacts are considered, and it is shown that downfall pressure magnitudes of 30–40 ρgH are regularly achieved. Dynamic impulse times of the events are also presented with higher-impact events generally relating to shorter impulse times, highlighting the dynamic character of these impacts. The largest downfall pressures are found to occur further from the vertical wall than previously measured. Importantly, the spray travelling furthest from the point of the initial wave impact on the vertical wall causes some of the largest downfall pressures on the deck. The paper concludes that, while the dataset is small, there are strong indications that the effects of these types of impacts are structurally significant and present a risk to infrastructure located landward of seawalls.

Identification of novel microcystins in algal extracts by a liquid chromatography–high-resolution mass spectrometry data analysis pipeline - Kirsten A. Cottrill; Christopher O. Miles; Logan C. Krajewski; Brady R. Cunningham; William Bragg; Noelani R. Boise; Kristin D. Victry; David S. Wunschel; Karen L. Wahl; Elizabeth I. Hamelin (Harmful Algae, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Sources of Li isotope bias during SIMS analysis of standard glasses - Adam C. Denny; Mindy M. Zimmer; Heather S. Cunningham; Natalie E. Sievers (Chemical Geology, 2024)

Sweet liking predicts liking and familiarity of some alcoholic beverages, but not alcohol intake: A population study using a split-sample approach - S. Spinelli; C. Cunningham; J. Prescott; E. Monteleone; C. Dinnella; C. Proserpio; T.L. White (Food Research International, 2024)

BASIS: BioAnalysis SEDFIT integrated software for cGMP analysis of SV-AUC data - Alexander E. Yarawsky; Erik S. Gough; Valeria Zai-Rose; Natalya I. Figueroa; Hazel M. Cunningham; John W. Burgner; Michael T. DeLion; Lake N. Paul (European Biophysics Journal, 2024)

Poorer inhibitory control was related to greater food intake across meals varying in portion size: A randomized crossover trial - Paige M. Cunningham; Liane S. Roe; Alaina L. Pearce; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2024)

Chemical cues of conspecific predation elicit distinct behavioural responses in cannibalistic poison frog tadpoles - Lisa L. Surber-Cunningham; Samta S. Oza; Eva K. Fischer (Animal Behaviour, 2024)

Reasons for meal termination, eating frequency, and typical meal context differ between persons with and without a spinal cord injury - Gary J. Farkas; Paige M. Cunningham; Alicia M. Sneij; John E. Hayes; Mark S. Nash; Arthur S. Berg; David R. Gater; Barbara J. Rolls (Appetite, 2024)

Pyrogeography in flux: Reorganization of Australian fire regimes in a hotter world - Calum X. Cunningham; Grant J. Williamson; Rachael H. Nolan; Lina Teckentrup; Matthias M. Boer; David M. J. S. Bowman (Global Change Biology, 2024)
Changes to the spatiotemporal patterns of wildfire are having profound implications for ecosystems and society globally, but we have limited understanding of the extent to which fire regimes will reorganize in a warming world. While predicting regime shifts remains challenging because of complex climate–vegetation–fire feedbacks, understanding the climate niches of fire regimes provides a simple way to identify locations most at risk of regime change. Using globally available satellite datasets, we constructed 14 metrics describing the spatiotemporal dimensions of fire and then delineated Australia's pyroregions—the geographic area encapsulating a broad fire regime. Cluster analysis revealed 18 pyroregions, notably including the (1) high‐intensity, infrequent fires of the temperate forests, (2) high‐frequency, smaller fires of the tropical savanna, and (3) low‐intensity, diurnal, human‐engineered fires of the agricultural zones. To inform the risk of regime shifts, we identified locations where the climate under three CMIP6 scenarios is projected to shift (i) beyond each pyroregion's historical climate niche, and (ii) into climate space that is novel to the Australian continent. Under middle‐of‐the‐road climate projections (SSP2‐4.5), an average of 65% of the extent of the pyroregions occurred beyond their historical climate niches by 2081–2100. Further, 52% of pyroregion extents, on average, were projected to occur in climate space without present‐day analogues on the Australian continent, implying high risk of shifting to states that also lack present‐day counterparts. Pyroregions in tropical and hot‐arid climates were most at risk of shifting into both locally and continentally novel climate space because (i) their niches are narrower than southern temperate pyroregions, and (ii) their already‐hot climates lead to earlier departure from present‐day climate space. Such a shift implies widespread risk of regime shifts and the emergence of no‐analogue fire regimes. Our approach can be applied to other regions to assess vulnerability to rapid fire regime change.

Variety and portion size combine to increase food intake at single-course and multi-course meals - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Introducing the Ecosystem and Socioeconomic Profile, a Proving Ground for Next Generation Stock Assessments - S. K. Shotwell; K. Blackhart; C. Cunningham; E. Fedewa; D. Hanselman; K. Aydin; M. Doyle; B. Fissel; P. Lynch; O. Ormseth; P. Spencer; S. Zador (Coastal Management, 2023)

The impact of greenfield residential development on mature trees - Cara R. Parsons; Saul Cunningham; Darren S. Le Roux; Philip Gibbons (Urban Forestry & Urban Greening, 2023)

Local tastes and global flavors: food choice in the context of the nutrition transition in South India - Asha Nadabar; Shailaja S. Patil; Ashlesha Datar; Rebecca Jones-Antwi; Solveig A. Cunningham (Food Security, 2023)

Field Investigation into Abrasion of Concrete at a Coastal Stepped Revetment: A U.K. Case Study - Nicholas Omoding; Lee S. Cunningham; Gregory F. Lane-Serff; Muhammad Omer; Brian Farrington (Journal of Marine Science and Engineering, 2023)
Although concrete abrasion damage is a major maintenance challenge for coastal structures fronted by beaches with hard coarse sediments, there are no readily available field studies that have measured abrasion damage of known concrete mixtures under defined exposure conditions. The objective of this investigation is to evaluate the abrasive exposure conditions of the concrete revetment armour units at Cleveleys on the Fylde coast of the U.K. and examine the feasibility of using terrestrial laser scanning (TLS) to measure concrete abrasion damage in field conditions. It was found that the concrete elements at Cleveleys are exposed to a macro-tidal environment, which experiences significant wave heights that vary from 0.42 to 1.92 m, whilst the peak wave periods range from 3.7 to 6.5 s. The beach sediments have a mean size of 26 mm and are moderately sorted. TLS provides a dense point cloud of abraded surfaces suitable for quantitative assessment of concrete abrasion in the field. Based on the measured abrasion depths and exposure durations, the peak concrete abrasion rates at the site varied from 3.5 to 4.5 mm/year, and severe abrasion was concentrated in the region between mean high-water springs and mean high-water neaps, wherein the highest beach levels were also found during the survey. Finally, the abraded surfaces exhibited a polished texture with no visible craters; thus, the mechanism of concrete material loss was by grinding/polishing due to rolling/sliding sediments.

Switching between bites of food and sips of water is related to food intake across meals varying in portion size - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Eating rate and bite size were related to food intake across meals varying in portion size: A randomized crossover trial in adults - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Anouk E.M. Hendriks-Hartensveld; Barbara J. Rolls (Appetite, 2023)

Development of EFNEP and SNAP-Ed Core Competencies in the Land-Grant University System - Susan S. Baker; Leslie Cunningham-Sabo; Karen Lillemor Franck; Kathryn McGirr; Janet Mullins (Journal of Nutrition Education and Behavior, 2023)

Experimental and Numerical Investigation of Floating Large Woody Debris Impact on a Masonry Arch Bridge - Eda Majtan; Lee S. Cunningham; Benedict D. Rogers (Journal of Marine Science and Engineering, 2022)
Masonry arch bridges form an essential part of existing transport infrastructure around the world, including mainland Europe and the northeastern US. Recent extreme flood events highlight that masonry arch bridges spanning watercourses are vulnerable to flood-induced hydrodynamic and debris impact loads. When the flow interacts with the bridge superstructure, with or without discrete floating debris, a complex interaction is observed. This paper presents both experimental and numerical studies to investigate this complex phenomenon, including fluid–structure and structure–structure interactions. A typical single-span masonry arch bridge and large woody debris representing a tree log are investigated. Experimental observations from a scaled hydraulic model, with and without debris in the flow, are first presented for the case where the abutment of the bridge is fully submerged. Next, the capability of the numerical method smoothed particle hydrodynamics (SPH) in simulating the hydrodynamic behaviour and debris impact observed in the experiment is discussed. Following this, both hydrodynamic and debris-induced pressure–time histories on the bridge are obtained using the SPH model. Results reveal that the debris impact leads to a significantly more localised load on the bridge compared to the situation with hydrodynamic load only.

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Heat increases full-length SMN splicing: promise for splice-augmenting therapies for SMA - Catherine E. Dominguez; David Cunningham; Akila S. Venkataramany; Dawn S. Chandler (Human Genetics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Numerical investigation of skimming flow characteristics over non-uniform gabion-stepped spillways - Ali Adel Zuhaira; Rwayda Kh. S. Al-Hamd; Saif Alzabeebee; Lee S. Cunningham (Innovative Infrastructure Solutions, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Measuring auditory cortical responses in Tursiops truncatus - Matt D. Schalles; Dorian S. Houser; James J. Finneran; Peter Tyack; Barbara Shinn-Cunningham; Jason Mulsow (Journal of Comparative Physiology A, 2021)
Auditory neuroscience in dolphins has largely focused on auditory brainstem responses; however, such measures reveal little about the cognitive processes dolphins employ during echolocation and acoustic communication. The few previous studies of mid- and long-latency auditory-evoked potentials (AEPs) in dolphins report different latencies, polarities, and magnitudes. These inconsistencies may be due to any number of differences in methodology, but these studies do not make it clear which methodological differences may account for the disparities. The present study evaluates how electrode placement and pre-processing methods affect mid- and long-latency AEPs in ( Tursiops truncatus ). AEPs were measured when reference electrodes were placed on the skin surface over the forehead, the external auditory meatus, or the dorsal surface anterior to the dorsal fin. Data were pre-processed with or without a digital 50-Hz low-pass filter, and the use of independent component analysis to isolate signal components related to neural processes from other signals. Results suggest that a meatus reference electrode provides the highest quality AEP signals for analyses in sensor space, whereas a dorsal reference yielded nominal improvements in component space. These results provide guidance for measuring cortical AEPs in dolphins, supporting future studies of their cognitive auditory processing.

Ordovician volcanic rocks record rifting, Variscan metamorphism and gold mineralization processes (Truchas Syncline, NW Iberia, Spain) - L. González-Menéndez; F. Gómez-Fernández; J. K. Cunningham; S. Menéndez; P. Caldevilla; G. Gallastegui; A. Cuesta (Journal of Iberian Geology, 2021)

GIS-based assessment of groundwater quality for drinking and irrigation purposes in central Iraq - Zaid F. Makki; Ali Adel Zuhaira; Sama M. Al-Jubouri; Rwayda Kh. S. Al-Hamd; Lee S. Cunningham (Environmental Monitoring and Assessment, 2021)

Stroke Induces Prolonged Changes in Lipid Metabolism, the Liver and Body Composition in Mice - Michael J. Haley; Claire S. White; Daisy Roberts; Kelly O’Toole; Catriona J. Cunningham; Jack Rivers-Auty; Conor O’Boyle; Conor Lane; Oliver Heaney; Stuart M. Allan; Catherine B. Lawrence (Translational Stroke Research, 2020)
During recovery, stroke patients are at risk of developing long-term complications that impact quality of life, including changes in body weight and composition, depression and anxiety, as well as an increased risk of subsequent vascular events. The aetiologies and time-course of these post-stroke complications have not been extensively studied and are poorly understood. Therefore, we assessed long-term changes in body composition, metabolic markers and behaviour after middle cerebral artery occlusion in mice. These outcomes were also studied in the context of obesity, a common stroke co-morbidity proposed to protect against post-stroke weight loss in patients. We found that stroke induced long-term changes in body composition, characterised by a sustained loss of fat mass with a recovery of lean weight loss. These global changes in response to stroke were accompanied by an altered lipid profile (increased plasma free fatty acids and triglycerides) and increased adipokine release at 60 days. After stroke, the liver also showed histological changes indicative of liver damage and a decrease in plasma alanine aminotransferase (ALT) was observed. Stroke induced depression and anxiety-like behaviours in mice, illustrated by deficits in exploration, nest building and burrowing behaviours. When initial infarct volumes were matched between mice with and without comorbid obesity, these outcomes were not drastically altered. Overall, we found that stroke induced long-term changes in depressive/anxiety-like behaviours, and changes in plasma lipids, adipokines and the liver that may impact negatively on future vascular health.

Growth and Sexual Dimorphism of the Hyoid Body in Macaca mulatta - Andreana S. Cunningham (International Journal of Primatology, 2020)

High temperatures are associated with substantial reductions in breeding success and offspring quality in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. Er; S. J. Cunningham (Oecologia, 2020)

A reintroduced ecosystem engineer provides a germination niche for native plant species - Catherine E. Ross; Sue McIntyre; Philip S. Barton; Maldwyn J. Evans; Saul A. Cunningham; Adrian D. Manning (Biodiversity and Conservation, 2020)

The costs of keeping cool: behavioural trade-offs between foraging and thermoregulation are associated with significant mass losses in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. J. Cunningham (Oecologia, 2019)

Projected changes in Brook Trout and Brown Trout distribution in Wisconsin streams in the mid-twenty-first century in response to climate change - Matthew G. Mitro; John D. Lyons; Jana S. Stewart; Paul K. Cunningham; Joanna D. T. Griffin (Hydrobiologia, 2019)

Demodicosis in a captive African straw-coloured fruit bat (Eidolon helvum) - Carlo Bianco; Kate S. Baker; Luca Pazzini; Alessandra Cafiso; Richard D. Suu-Ire; Andrew A. Cunningham; James L. N. Wood; Alejandro Nuñez (Experimental and Applied Acarology, 2019)

Vitellogenesis in spiders: first analysis of protein changes in different reproductive stages of Polybetes pythagoricus - S. Romero; A. Laino; F. Arrighetti; C. F. García; M. Cunningham (Journal of Comparative Physiology B, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Frequency, duration and severity of drought in the Semiarid Northeast Brazil region - S. S. B. Brito; A. P. M. A. Cunha; C. C. Cunningham; R. C. Alvalá; J. A. Marengo; M. A. Carvalho (International Journal of Climatology, 2018)
Drought is the natural disaster that impacts the greatest number of people and produces the most significant economic losses. This work presents a quantitative assessment of drought events occurred in the Semiarid region of Northeast Brazil during 1981–2016. The purpose of this study is to provide an overview of drought intensity for the last 36 years, analysing their severity, frequency and duration, considering hydro‐meteorological and agricultural aspects. To evaluate these two aspects, the 12‐month standardized precipitation index and the vegetation health index were considered to investigate drought characteristics. The definition of drought event for both these indices was performed regarding start and end month. In this context, drought duration is considered equal to the number of months of event, drought frequency is the number of events per time period and the drought severity is the absolute value of integral area below zero. Results show that the most severe and prolonged drought occurred in 2011–2016. In a clear contrast to previous droughts in past decades, during these last 5‐years period drought were more frequent, severe and affected a larger area with significant impacts for population, as well as economical activities.

SMN regulation in SMA and in response to stress: new paradigms and therapeutic possibilities - Catherine E. Dominguez; David Cunningham; Dawn S. Chandler (Human Genetics, 2017)

The effect of motor overflow on bimanual asymmetric force coordination - David A. Cunningham; Sarah M. Roelle; Didier Allexandre; Kelsey A. Potter-Baker; Vishwanath Sankarasubramanian; Jayme S. Knutson; Guang H. Yue; Andre G. Machado; Ela B. Plow (Experimental Brain Research, 2017)

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Serosurvey of canine distemper virus and canine parvovirus in wild canids and domestic dogs at the rural interface in the Coquimbo Region, Chile - G. Acosta-Jamett; A. A. Cunningham; B. M. deC. Bronsvoort; S. Cleaveland (European Journal of Wildlife Research, 2015)

Does morphology predict trophic position and habitat use of ant species and assemblages? - H. Gibb; J. Stoklosa; D. I. Warton; A. M. Brown; N. R. Andrew; S. A. Cunningham (Oecologia, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Physicochemical and Formulation Developability Assessment for Therapeutic Peptide Delivery—A Primer - Annette Bak; Dennis Leung; Stephanie E. Barrett; Seth Forster; Ellen C. Minnihan; Andrew W. Leithead; James Cunningham; Nathalie Toussaint; Louis S. Crocker (The AAPS Journal, 2015)

Discriminative stimulus and hypothermic effects of some derivatives of the nAChR agonist epibatidine in mice - Jesse S. Rodriguez; Colin S. Cunningham; Fernando B. Moura; Pauline Ondachi; F. Ivy Carroll; Lance R. McMahon (Psychopharmacology, 2014)

Sterol Carrier Protein-2: Binding Protein for Endocannabinoids - Elizabeth Sabens Liedhegner; Caleb D. Vogt; Daniel S. Sem; Christopher W. Cunningham; Cecilia J. Hillard (Molecular Neurobiology, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

Grassland area determines beetle assemblage dissimilarity from surrounding floodplain forest - Philip S. Barton; Matthew J. Colloff; Kimberi R. Pullen; Saul A. Cunningham (Journal of Insect Conservation, 2013)

Arthropod assemblages in a focal tree species (Eucalyptus microcarpa) depends on the species mix in restoration plantings - Philip S. Barton; Matthew J. Colloff; Kimberi R. Pullen; Saul A. Cunningham (Biodiversity and Conservation, 2013)

Multiple nicotine training doses in mice as a basis for differentiating the effects of smoking cessation aids - Colin S. Cunningham; Lance R. McMahon (Psychopharmacology, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

The role of carrion in maintaining biodiversity and ecological processes in terrestrial ecosystems - Philip S. Barton; Saul A. Cunningham; David B. Lindenmayer; Adrian D. Manning (Oecologia, 2013)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Fine‐scale heterogeneity in beetle assemblages under co‐occurring Eucalyptus in the same subgenus - Philip S. Barton; Adrian D. Manning; Heloise Gibb; David B. Lindenmayer; Saul A. Cunningham (Journal of Biogeography, 2010)
Aim Insect biodiversity is often positively associated with habitat heterogeneity. However, this relationship depends on spatial scale, with most studies focused on differences between habitats at large scales with a variety of forest tree species. We examined fine‐scale heterogeneity in ground‐dwelling beetle assemblages under co‐occurring trees in the same subgenus: Eucalyptus melliodora A. Cunn. ex Schauer and E. blakelyi Maiden (Myrtaceae). Location Critically endangered grassy woodland near Canberra, south‐eastern Australia. Methods We used pitfall traps and Tullgren funnels to sample ground‐dwelling beetles from the litter environment under 47 trees, and examined differences in diversity and composition at spatial scales ranging from 100 to 1000 m. Results Beetle assemblages under the two tree species had distinctive differences in diversity and composition. We found that E. melliodora supported a higher richness and abundance of beetles, but had higher compositional similarity among samples. In contrast, E. blakelyi had a lower abundance and species richness of beetles, but more variability in species composition among samples. Main conclusions Our study shows that heterogeneity in litter habitat under co‐occurring and closely related eucalypt species can influence beetle assemblages at spatial scales of just hundreds of metres. The differential contribution to fine‐scale alpha and beta diversity by each eucalypt can be exploited for conservation purposes by ensuring an appropriate mix of the two species in the temperate woodlands where they co‐occur. This would help not only to maximize biodiversity at landscape scales, but also to maintain heterogeneity in species richness, trophic function and biomass at fine spatial scales.

Endotoxin-induced HIF-1α stabilisation in equine endothelial cells: synergistic action with hypoxia - A. C. Brooks; N. Menzies-Gow; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2010)

Impact of hydrographic data assimilation on the modelled Atlantic meridional overturning circulation - G. C. Smith; K. Haines; T. Kanzow; S. Cunningham (Ocean Science, 2010)
Here we make an initial step toward the development of an ocean assimilation system that can constrain the modelled Atlantic Meridional Overturning Circulation (AMOC) to support climate predictions. A detailed comparison is presented of 1° and 1/4° resolution global model simulations with and without sequential data assimilation, to the observations and transport estimates from the RAPID mooring array across 26.5° N in the Atlantic. Comparisons of modelled water properties with the observations from the merged RAPID boundary arrays demonstrate the ability of in situ data assimilation to accurately constrain the east-west density gradient between these mooring arrays. However, the presence of an unconstrained "western boundary wedge" between Abaco Island and the RAPID mooring site WB2 (16 km offshore) leads to the intensification of an erroneous southwards flow in this region when in situ data are assimilated. The result is an overly intense southward upper mid-ocean transport (0–1100 m) as compared to the estimates derived from the RAPID array. Correction of upper layer zonal density gradients is found to compensate mostly for a weak subtropical gyre circulation in the free model run (i.e. with no assimilation). Despite the important changes to the density structure and transports in the upper layer imposed by the assimilation, very little change is found in the amplitude and sub-seasonal variability of the AMOC. This shows that assimilation of upper layer density information projects mainly on the gyre circulation with little effect on the AMOC at 26° N due to the absence of corrections to density gradients below 2000 m (the maximum depth of Argo). The sensitivity to initial conditions was explored through two additional experiments using a climatological initial condition. These experiments showed that the weak bias in gyre intensity in the control simulation (without data assimilation) develops over a period of about 6 months, but does so independently from the overturning, with no change to the AMOC. However, differences in the properties and volume transport of North Atlantic Deep Water (NADW) persisted throughout the 3 year simulations resulting in a difference of 3 Sv in AMOC intensity. The persistence of these dense water anomalies and their influence on the AMOC is promising for the development of decadal forecasting capabilities. The results suggest that the deeper waters must be accurately reproduced in order to constrain the AMOC.

The contribution of eastern-boundary density variations to the Atlantic meridional overturning circulation at 26.5° N - M. P. Chidichimo; T. Kanzow; S. A. Cunningham; W. E. Johns; J. Marotzke (Ocean Science, 2010)
We study the contribution of eastern-boundary density variations to sub-seasonal and seasonal anomalies of the strength and vertical structure of the Atlantic Meridional Overturning Circulation (AMOC) at 26.5° N, by means of the RAPID/MOCHA mooring array between April 2004 and October 2007. The major density anomalies are found in the upper 500 m, and they are often coherent down to 1400 m. The densities have 13-day fluctuations that are apparent down to 3500 m. The two strategies for measuring eastern-boundary density – a tall offshore mooring (EB1) and an array of moorings on the continental slope (EBH) – show little correspondence in terms of amplitude, vertical structure, and frequency distribution of the resulting basin-wide integrated transport fluctuations, implying that there are significant transport contributions between EB1 and EBH. Contrary to the original planning, measurements from EB1 cannot serve as backup or replacement for EBH: density needs to be measured directly at the continental slope to compute the full-basin density gradient. Fluctuations in density at EBH generate transport variability of 2 Sv rms in the AMOC, while the overall AMOC variability is 4.8 Sv rms. There is a pronounced deep-reaching seasonal cycle in density at the eastern boundary, which is apparent between 100 m and 1400 m, with maximum positive anomalies in spring and maximum negative anomalies in autumn. These changes drive anomalous southward upper mid-ocean flow in spring, implying maximum reduction of the AMOC, and vice-versa in autumn. The amplitude of the seasonal cycle of the AMOC arising from the eastern-boundary densities is 5.2 Sv peak-to-peak, dominating the 6.7 Sv peak-to-peak seasonal cycle of the total AMOC. Our analysis suggests that the seasonal cycle in density may be forced by the strong near-coastal seasonal cycle in wind stress curl.

Factors driving pathogenicity vs. prevalence of amphibian panzootic chytridiomycosis in Iberia - Susan F. Walker; Jaime Bosch; Virgilio Gomez; Trenton W. J. Garner; Andrew A. Cunningham; Dirk S. Schmeller; Miguel Ninyerola; Daniel A. Henk; Cedric Ginestet; Christian‐Philippe Arthur; Matthew C. Fisher (Ecology Letters, 2010)
Ecology Letters (2010) 13: 372–382 Abstract Amphibian chytridiomycosis is a disease caused by the fungus Batrachochytrium dendrobatidis ( Bd ). Whether Bd is a new emerging pathogen (the novel pathogen hypothesis; NPH) or whether environmental changes are exacerbating the host‐pathogen dynamic (the endemic pathogen hypothesis; EPH) is debated. To disentangle these hypotheses we map the distribution of Bd and chytridiomycosis across the Iberian Peninsula centred on the first European outbreak site. We find that the infection‐free state is the norm across both sample sites and individuals. To analyse this dataset, we use Bayesian zero‐inflated binomial models to test whether environmental variables can account for heterogeneity in both the presence and prevalence of Bd, and heterogeneity in the occurrence of the disease, chytridiomycosis. We also search for signatures of Bd ‐spread within Iberia using genotyping. We show (1) no evidence for any relationship between the presence of Bd and environmental variables, (2) a weak relationship between environmental variables and the conditional prevalence of infection, (3) stage‐dependent heterogeneity in the infection risk, (4) a strong association between altitude and chytridiomycosis, (5) multiple Iberian genotypes and (6) recent introduction and spread of a single genotype of Bd in the Pyrenees. We conclude that the NPH is consistent with the emergence of Bd in Iberia. However, epizootic forcing of infection is tied to location and shaped by both biotic and abiotic variables. Therefore, the population‐level consequences of disease introduction are explained by EPH‐like processes. This study demonstrates the power of combining surveillance and molecular data to ascertain the drivers of new emerging infections diseases.

Corrigendum to "Observed and simulated estimates of the meridional overturning circulation at 26.5° N in the Atlantic" published in Ocean Sci., 5, 575–589, 2009 - J. Baehr; S. Cunningham; H. Haak; P. Heimbach; T. Kanzow; J. Marotzke (Ocean Science, 2010)

Does the availability of arboreal honeydew determine the prevalence of ecologically dominant ants in restored habitats? - H. Gibb; S. A. Cunningham (Insectes Sociaux, 2009)

Adjustment of the basin-scale circulation at 26° N to variations in Gulf Stream, deep western boundary current and Ekman transports as observed by the Rapid array - H. L. Bryden; A. Mujahid; S. A. Cunningham; T. Kanzow (Ocean Science, 2009)
The Rapid instrument array across the Atlantic Ocean along 26° N provides unprecedented monitoring of the basin-scale circulation. A unique feature of the Rapid array is the combination of full-depth moorings with instruments measuring temperature, salinity, pressure time series at many depths with co-located bottom pressure measurements so that dynamic pressure can be measured from surface to bottom. Bottom pressure measurements show a zonally uniform rise (and fall) of bottom pressure of 0.015 dbar on a 5 to 10 day time scale, suggesting that the Atlantic basin is filling and draining on a short time scale. After removing the zonally uniform bottom pressure fluctuations, bottom pressure variations at 4000 m depth against the western boundary compensate instantaneously for baroclinic fluctuations in the strength and structure of the deep western boundary current so there is no basin-scale mass imbalance resulting from variations in the deep western boundary current. After removing the mass compensating bottom pressure, residual bottom pressure fluctuations at the western boundary just east of the Bahamas balance variations in Gulf Stream transport. Again the compensation appears to be especially confined close to the western boundary. Thus, fluctuations in either Gulf Stream or deep western boundary current transports are compensated in a depth independent (barotropic) manner very close to the continental slope off the Bahamas. In contrast, compensation for variations in wind-driven surface Ekman transport appears to involve fluctuations in both western basin and eastern basin bottom pressures, though the bottom pressure difference fluctuations appear to be a factor of 3 too large, perhaps due to an inability to resolve small bottom pressure fluctuations after removal of larger zonal average, baroclinic, and Gulf Stream pressure components. For 4 tall moorings where time series dynamic height (geostrophic pressure) profiles can be estimated from sea surface to ocean bottom and bottom pressure can be added, there is no general correlation between surface dynamic height and bottom pressure. Dynamic height on each mooring is strongly correlated with sea surface height from satellite observations and the variability in both dynamic height and satellite sea surface height decrease sharply as the western boundary is approached.

A Robust Technique for Mapping Vegetation Condition Across a Major River System - S. C. Cunningham; R. Mac Nally; J. Read; P. J. Baker; M. White; J. R. Thomson; P. Griffioen (Ecosystems, 2009)

Reference-dose place conditioning with ethanol in mice: empirical and theoretical analysis - Peter A. Groblewski; Laura S. Bax; Christopher L. Cunningham (Psychopharmacology, 2008)

Landscape effects on crop pollination services: are there general patterns? - Taylor H. Ricketts; James Regetz; Ingolf Steffan‐Dewenter; Saul A. Cunningham; Claire Kremen; Anne Bogdanski; Barbara Gemmill‐Herren; Sarah S. Greenleaf; Alexandra M. Klein; Margaret M. Mayfield; Lora A. Morandin; Alfred Ochieng’; et al. (Ecology Letters, 2008)
Pollination by bees and other animals increases the size, quality, or stability of harvests for 70% of leading global crops. Because native species pollinate many of these crops effectively, conserving habitats for wild pollinators within agricultural landscapes can help maintain pollination services. Using hierarchical Bayesian techniques, we synthesize the results of 23 studies – representing 16 crops on five continents – to estimate the general relationship between pollination services and distance from natural or semi‐natural habitats. We find strong exponential declines in both pollinator richness and native visitation rate. Visitation rate declines more steeply, dropping to half of its maximum at 0.6 km from natural habitat, compared to 1.5 km for richness. Evidence of general decline in fruit and seed set – variables that directly affect yields – is less clear. Visitation rate drops more steeply in tropical compared with temperate regions, and slightly more steeply for social compared with solitary bees. Tropical crops pollinated primarily by social bees may therefore be most susceptible to pollination failure from habitat loss. Quantifying these general relationships can help predict consequences of land use change on pollinator communities and crop productivity, and can inform landscape conservation efforts that balance the needs of native species and people.

A cDNA Microarray for Crassostrea virginica and C. gigas - Matthew J. Jenny; Robert W. Chapman; Annalaura Mancia; Yian A. Chen; David J. McKillen; Hal Trent; Paul Lang; Jean-Michel Escoubas; Evelyne Bachere; Viviane Boulo; Z. John Liu; Paul S. Gross; et al. (Marine Biotechnology, 2007)

Endotoxin-induced activation of equine platelets: evidence for direct activation of p38 MAPK pathways and vasoactive mediator production - A. C. Brooks; N. J. Menzies-Gow; C. Wheeler-Jones; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2007)

New Resources for Marine Genomics: Bacterial Artificial Chromosome Libraries for the Eastern and Pacific Oysters (Crassostrea virginica and C. gigas) - Charles Cunningham; Jun-ichi Hikima; Matthew J. Jenny; Robert W. Chapman; Guang-Chen Fang; Chris Saski; Mats L. Lundqvist; Rod A. Wing; Pauline M. Cupit; Paul S. Gross; Greg W. Warr; Jeff P. Tomkins (Marine Biotechnology, 2006)

Feline Immunodeficiency Virus and Puma Lentivirus in Florida panthers (Puma concolor coryi): Epidemiology and Diagnostic Issues - D. L. Miller; S. K. Taylor; D. S. Rotstein; M. B. Pough; M. C. Barr; C. A. Baldwin; M. Cunningham; M. Roelke; D. Ingram (Veterinary Research Communications, 2006)

Characterisation of the European Marine Sites in South West England: The Fal and Helford Candidate Special Area of Conservation (cSAC) - W. J. Langston; B. S. Chesman; G. R. Burt; M. Taylor; R. Covey; N. Cunningham; P. Jonas; S. J. Hawkins (Hydrobiologia, 2006)

Infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland: virus identification, histopathology, immunohistochemistry and genetic comparison with Scottish mainland isolates - D A Smail; N Bain; D W Bruno; J A King; F Thompson; D J Pendrey; S Morrice; C O Cunningham (Journal of Fish Diseases, 2006)
During mid‐June 1999 peak mortalities of 11% of the total stock per week were seen at a sea cage site of Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland. Virus was isolated on chinook salmon embryo (CHSE) cells in a standard diagnostic test and infectious pancreatic necrosis virus (IPNV) identified by enzyme‐linked immunosorbent assay. IPNV was confirmed as serogroup A by a cell immunofluorescent antibody test using the cross‐reactive monoclonal antibody AS‐1. Four weeks after the main outbreak, virus titres in surviving moribund fish were assayed at >10 10 TCID 50 g −1 kidney. Histopathology of moribund fish was characterized by pancreatic acinar cell necrosis and a marked catarrhal enteritis of the intestinal mucosa. In the liver, necrosis, leucocytic infiltration and a generalized cell vacuolation were noted. IPNV‐specific immunostaining was demonstrated in pancreas, liver, heart, gill and kidney tissue. The nucleotide sequence of the coding region of segment A was determined from the Shetland isolate. A 1180 bp fragment of the VP2 gene of this isolate was compared with a 1979 reference isolate from mainland Scottish Atlantic salmon, La/79 and another more recent mainland isolate, 432/00. Both A2 isolates were derived from carrier fish without signs of IPN and serotyped by a plaque neutralization test. The Shetland isolate shows a different nucleotide and amino acid sequence compared with the two isolates from carrier fish. These latter isolates showed identical amino acid sequences in the fragment examined, despite the 21 years separating the isolations. Sequence comparisons with other A2 (Sp) isolates on the database confirm all three Scottish isolates are A2 (Sp).

GABA-benzodiazepine receptor function in alcohol dependence: a combined 11C-flumazenil PET and pharmacodynamic study - A. R. Lingford-Hughes; S. J. Wilson; V. J. Cunningham; A. Feeney; B. Stevenson; D. J. Brooks; D. J. Nutt (Psychopharmacology, 2005)

Phosphate nutrition effects on growth, phosphate transporter transcript levels and physiology of alfalfa cells - S. F. Abu. Qamar; T. G. Sors; S. M. Cunningham; B. C. Joern; J. J. Volenec (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Photosynthetic responses to vapour pressure deficit in temperate and tropical evergreen rainforest trees of Australia - S. C. Cunningham (Oecologia, 2005)

Effects of dopamine D 1 - or D 2 -like receptor antagonists on the hypermotive and discriminative stimulus effects of (+)-MDMA - Marcy J. Bubar; Kami M. Pack; Paul S. Frankel; Kathryn A. Cunningham (Psychopharmacology, 2004)

Reduced recombination in maternal meiosis coupled with non-disjunction at meiosis II leading to recurrent 47,XXX - Orit Reish; Todd Berryman; Thomas R. Cunningham; Carron Sher; William S. Oetting (Chromosome Research, 2004)

Increased risk for developmental delay in Saethre-Chotzen syndrome is associated with TWIST deletions: an improved strategy for TWIST mutation screening - Juanliang Cai; Barbara K. Goodman; Ankita S. Patel; John B. Mulliken; Lionel Van Maldergem; George E. Hoganson; William A. Paznekas; Ziva Ben-Neriah; Ruth Sheffer; Michael L. Cunningham; Donna L. Daentl; Ethylin Wang Jabs (Human Genetics, 2003)

The sodium channel blocker RS100642 reverses down-regulation of the sodium channel α-subunit Nav 1.1 expression caused by transient ischemic brain injury in rats - C. Yao; A. J. Williams; X. -C. M. Lu; R. A. Price; B. S. Cunningham; R. Berti; F. C. Tortella; J. R. Dave (Neurotoxicity Research, 2003)

Comparison of temperate and tropical rainforest tree species: growth responses to temperature - S. Cunningham; J. Read (Journal of Biogeography, 2003)
Aim To investigate whether the latitudinal distribution of rainforest trees in Australia can be explained by their growth responses to temperature. Methods The rainforest canopy trees Acmena smithii (Poir.) Merrill & Perry, Alstonia scholaris (L.) R. Br., Castanospermum australe Cunn. & C. Fraser ex Hook., Eucryphia lucida (Labill.) Baill., Heritiera trifoliolata (F. Muell.) Kosterm., Nothofagus cunninghamii (Hook.) Oerst., Sloanea woollsii F. Muell. and Tristaniopsis laurina (Sm.) Wilson & Waterhouse were selected to cover the latitudinal range of rainforests in eastern Australia. Seedlings of these species were grown under a range of day/night temperature regimes (14/6, 19/11, 22/14, 25/17, and 30/22 °C) in controlled‐environment cabinets. These seedlings were harvested after 16 weeks to determine differences in growth rate and biomass allocation among species and temperature regimes. Results The temperate species showed maximum growth at lower temperatures than the tropical species. However, there was considerable overlap in the growth rates of the temperate and tropical rainforest types across the temperature range used. Maximum growth of the tropical rainforest types was associated with changes in biomass allocation whereas the temperate rainforest types showed no significant changes in biomass allocation across the temperature range. Main conclusions All species showed temperatures for maximum growth that were considerably higher than those previously shown for maximum net photosynthesis. The growth responses to temperature of the rainforest species under these experimental conditions provided limited evidence for their restriction to certain latitudes. These growth responses to temperature showed that the physiological assumptions used in various types of vegetation‐climate models may not be true of Australian rainforest trees.

Comparison of temperate and tropical rainforest tree species: photosynthetic responses to growth temperature - S. Cunningham; J. Read (Oecologia, 2002)

Refuting a controversial case of a human‐mediated marine species introduction - John P. Wares; Deena S. Goldwater; Bo Y. Kong; Clifford W. Cunningham (Ecology Letters, 2002)
Human activities have strongly impacted natural communities through the introduction of non‐native species in historical times. A frequently cited marine example is Littorina littorea , a common intertidal gastropod that was first reported in North America in 1840. The seemingly sudden appearance and rapid geographical spread of this species southward from Nova Scotia has led many researchers to consider L. littorea a human‐mediated species introduction. This is despite allozyme and subfossil evidence that the `European periwinkle' was in North America long before 1840. Our mitochondrial and nuclear DNA sequence data confirm that L. littorea has been in continuous residence in North America for at least 8000 years. It appears most likely that ecological interactions, rather than oceanographic or climatic forces, maintained the limited geographical distribution of L. littorea prior to the 19th century.

Cryopreservation of alfalfa (Medicago sativa L.) cells by encapsulation-dehydration - R. Shibli; D. Haagenson; S. Cunningham; W. Berg; J. Volenec (Plant Cell Reports, 2001)

Ion Permeation and Selectivity of Wild-Type Recombinant Rat CNG (rOCNC1) Channels Expressed in HEK293 Cells - W. Qu; X.O. Zhu; A.J. Moorhouse; S. Bieri; A.M. Cunningham; P.H. Barry (The Journal of Membrane Biology, 2000)

Molecular cloning of the gene for interleukin-1? from Xenopus laevis and analysis of expression in vivo and in vitro - J. Zou; S. Bird; C. Cunningham; C. J. Secombes; J. Horton; R. Minter (Immunogenetics, 2000)

Comparative Effects of Ambient Ultraviolet‐B Radiation on Two Sympatric Species of Australian Frogs - Sara D. Broomhall; William S. Osborne; Ross B. Cunningham (Conservation Biology, 2000)
Declines have been observed in a number of Australian frog species, many of these at high elevations. Alpine regions in Australia are likely to be particularly subject to increases in ultraviolet‐B radiation ( UV‐B, 280–320 nm) because UV‐B levels increase with elevation and because anthropogenic depletion of ozone has been particularly severe in the southern hemisphere. We compared survivorship of embryos and tadpoles of a declining species of frog, Litoria verreauxii alpina , with those of a sympatric nondeclining species, Crinia signifera , under three ambient UV‐B treatments, unshielded, control, and UV‐B–excluding. Experiments were conducted in artificial water bodies established at three different elevations (1365, 1600, and 1930 m) in the Snowy Mountains of southeastern Australia. The exclusion of UV‐B significantly enhanced survival of L. v. alpina (declining species) at all elevations. Overall, the probability of dying was highest in the unshielded treatments and lowest under the UV‐B–excluding treatment for both species over all elevations. The probability of dying was significantly higher in L. v. alpina than in C. signifera for a given UV‐B treatment at the two highest elevations. Our results support the hypothesis that ultraviolet radiation is likely to be a contributing factor in the disappearance of L. v. alpina at high elevations in southern Australia.

Comparative studies of piscine and amphibian iridoviruses - A. D. Hyatt; A. R. Gould; Z. Zupanovic; A. A. Cunningham; S. Hengstberger; R. J. Whittington; J. Kattenbelt; B. E. H. Coupar (Archives of Virology, 2000)

Reply to the comment by C.S. Spirakis - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1999)

LONG DISTANCE OFFSHORE MOVEMENTS OF BOTTLENOSE DOLPHINS 1 - Randall S. Wells; Howard L. Rhinehart; Petra Cunningham; Joanne Whaley; Melody Baran; Chris Koberna; Daniel P. Costa (Marine Mammal Science, 1999)
A bstract Despite recent progress defining the morphological and genetic characteristics of forms of the bottlenose dolphin inhabiting offshore waters, little is known of their behavior or ranging patterns. Reports suggest that an “offshore form” exists between the 200‐ and 2,000‐m isobaths in distinct Gulf of Mexico and western North Atlantic stocks, while one or more coastal forms inhabit the waters inshore. Two opportunities to track rehabilitated adult male bottlenose dolphins with satellite‐linked transmitters occurred in 1997. “Rudy” stranded in NW Florida and was released in the Gulf of Mexico off central west Florida. He moved around Florida and northward to off Cape Hatteras, NC, covering 2,050 km in 43 d. “Gulliver” stranded near St. Augustine and was released off Cape Canaveral, FL. He moved 4,200 km in 47 d to a location northeast of the Virgin Islands. Gulliver swam through 5,000‐m‐deep waters 300 km offshore of the northern Caribbean islands, against the North Equatorial Current. These records expand the range and habitat previously reported for the offshore stock of bottlenose dolphins inhabiting the waters off the southeastern United States, underscore the difficulties of defining pelagic stocks, illustrate the success of rehabilitation efforts, indicate the value of follow‐up monitoring of rehabilitated and released cetaceans, and expand our understanding of the long‐range movement capabilities of a dolphin species more commonly thought of as a resident in coastal waters.

Genetic differences in cocaine-induced conditioned place preference in mice depend on conditioning trial duration - Christopher L. Cunningham; Shelly D. Dickinson; Nicholas J. Grahame; Dobrina M. Okorn; Carrie S. McMullin (Psychopharmacology, 1999)

Sheep CD4 + αβ T cells express novel members of the T19 multigene family - Meredith A. O'Keeffe; S. A. Metcalfe; Craig P. Cunningham; I. D. Walker (Immunogenetics, 1999)

Hydrothermal uranium deposits containing molybdenum and fluorite in the Marysvale volcanic field, west-central Utah - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1998)

Analysis of the human Sonic Hedgehog coding and promoter regions in sacral agenesis, triphalangeal thumb, and mirror polydactyly - F. R. Vargas; E. Roessler; Karin Gaudenz; E. Belloni; Alexander S. Whitehead; Peader N. Kirke; James L. Mills; George Hooper; Roger E. Stevenson; Isabel Cordeiro; Patricia Correia; Temis Felix; et al. (Human Genetics, 1998)

Flavor preference conditioning by oral self-administration of ethanol - Christopher L. Cunningham; Jill S. Niehus (Psychopharmacology, 1997)

The carcinogenicity of diethylstilbestrol: structural evidence for a non-genotoxic mechanism - A. Cunningham; G. Klopman; H. S. Rosenkranz (Archives of Toxicology, 1996)

Portage: A new early-maturing, round white table potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1995)

Prestile: A new round white potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1994)

Hydrolysis of oleylanilide in the rat - V. J. Cunningham; S. P. Tucker; E. Bailey (Archives of Toxicology, 1983)

Variation in the hepatotoxic effects of carbon disulphide between different strains of rat - S. P. Tucker; D. P. Lovell; A. A. Seawright; V. J. Cunningham (Archives of Toxicology, 1980)

Erratum - I. L. Nonnecke; W. E. Torfason; L. C. Young; P. Nandi; S. P. Raychaudhuri; Helen H. Cunningham; Mary V. Zaehringer; Walter C. Sparks; Clarence J. Miller; Richard L Sawyer (American Journal of Potato Research, 1966)

Effect of sprout inhibitors on the incidence of Fusarium dry rot and sprouting of potato tubers - J. Howard Ellison; H. S. Cunningham (American Journal of Potato Research, 1953)

Effect of soil reaction on the performance of certain scab-resistant and susceptible potato varieties - J. H. Ellison; W. C. Jacob; H. S. Cunningham (American Journal of Potato Research, 1951)

The addition of mercury compounds to the fertilizer mixture as a control for common scab of the potato under Long Island conditions - H. S. Cunningham (American Journal of Potato Research, 1936)